2010
DOI: 10.1111/j.1439-0396.2009.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of twinning on milk yield, dystocia, calf birth weight and open days in Holstein dairy cows of Iran

Abstract: Calving records of Iranian Holsteins from April 1998 to September 2006 comprising 16 herds with 104,572 calving events representing 4045 twin births were used to evaluate reported open days, calving difficulties and calf birth weight in single- and twin-births and the relationship exists between twinning and milk production. A logistic regression model was constructed to analyse dystocia for single- and twin-births. In addition, statistical analyses of 305-day milk yield, open days and calf birth weight were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
2
22
2
1
Order By: Relevance
“…FSCR averaged 28.4% in services following first calving, 23.9% in services following second calving and 19.8% in services following third calving. The average of DO in this study was consistent with the result of the previous study (Ghavi Hossein-Zadeh, 2010) which reported the average of DO as 137.08 in Iranian Holsteins. DCFS is highly affected by the length of the voluntary waiting period, which differs among herds and among management groups within a herd.…”
Section: Resultssupporting
confidence: 92%
“…FSCR averaged 28.4% in services following first calving, 23.9% in services following second calving and 19.8% in services following third calving. The average of DO in this study was consistent with the result of the previous study (Ghavi Hossein-Zadeh, 2010) which reported the average of DO as 137.08 in Iranian Holsteins. DCFS is highly affected by the length of the voluntary waiting period, which differs among herds and among management groups within a herd.…”
Section: Resultssupporting
confidence: 92%
“…For example, the risk of pregnancy loss during the first trimester of gestation for cows carrying twins is three to nine times higher than for cows carrying singletons (López-Gatius et al, 2002, 2009López-Gatius & García-Ispierto, 2010). Higher milk production related to twinning is controversial (Beerepoot et al, 1992;Bicalho et al, 2007;Ghavi Hossein-Zadeh, 2010b), and this possible benefit will never outweigh the higher incidence of dystocia, stillbirths, and retained placenta (Beerepoot et al, 1992;Echternkamp & Gregory, 1999). Wiltbank et al (2000) proposed that high milk production increases steroid metabolism as a result of an increased blood flow to the digestive tract and the liver.…”
Section: Twinningmentioning
confidence: 99%
“…Adequate body condition score at calving for both primiparous and multiparous dams (BCS of 2.5 to 3, when assessed on a 5 point scale) ensures optimization of ease of delivery and subsequent performance. Primiparous cows are known to have greater risk of difficulty than multiparous cows (Ghavi Hossein-Zadeh, 2010b;Gaafar et al, 2011), partly because of their smaller size and pelvic size. It is recommended that first calving takes place between 22 to 24 months of age to optimize subsequent performance and ease of delivery (Le Cozler et al, 2008;Berry & Cromie, 2009).…”
Section: Dystociamentioning
confidence: 99%
See 2 more Smart Citations